Depression, disability and functional status among community‐dwelling older adults in South Africa: evidence from the first South African National Income Dynamics Study. (20th March 2013) - Tomita, Andrew; Burns, Jonathan K.
Abstract : Objectives: This study examined the relationship between depression and functional status among a community‐dwelling older population of 65 years and older in South Africa. Method: Data from the first wave of the South African National Income Dynamics Study were used, this being the first longitudinal panel survey of a nationally representative sample of households. The study focused on the data for resident adults 65 years and older ( n  = 1, 429). Depression was assessed using the 10‐item version of the Center for Epidemiologic Studies Depression Scale. Functional status, pertaining to both difficulty and dependence in activities of daily living (ADL), instrumental activities of daily living (IADL), and physical functioning and mobility (PFM), were assessed using 11 items. Results: Functional challenges were generally higher in the older age group. There was a significant association between depression and functional dependence in ADL (adjusted OR = 2.57 [CI: 1.03–6.41]), IADL (adjusted OR = 2.76 [CI: 1.89–4.04]), and PFM (adjusted OR = 1.66 [CI: 1.18–2.33]), but the relationship between depression and functional status, particularly PFM, appeared weaker in older age. Conclusion: The relationship between depression symptoms and function is complex. Functional characteristics between older and younger old populations are diverse, and caution is indicated against overgeneralizing the challenges related to depression and function among this target population. Copyright © 2013 John Wiley & Sons, Ltd.